The Influence of Human Resource Quality on Employee Performance at the Gantarang Sub-District Office, Bulukumba Regency - Ina Ramadhani; Muchriady Muchran; Andi Risfan Rizaldi (Economos : Jurnal Ekonomi dan Bisnis, 2025)
Human resources are the main asset in an organization that determines the success of achieving goals, including in government institutions. This study aims to examine the influence of human resource quality on employee performance at the Gantarang Sub-district Office, Bulukumba Regency. A quantitative research design was employed by involving the entire population of 40 employees as respondents through purposive sampling, considering that all members of the population met the research criteria. Data were collected using questionnaires and analyzed through simple linear regression and a partial test (t-test) with the assistance of SPSS version 26. The results show that human resource quality has a positive and significant effect on employee performance, indicating that improvements in employees’ knowledge, skills, and attitudes contribute directly to better performance outcomes. These findings strengthen the theoretical perspective that human capital is a central factor in enhancing organizational effectiveness. The study concludes that efforts to strengthen employee competencies, provide training, and create a supportive work environment are essential strategies for improving public service performance in government institutions such as the Gantarang Sub-district Office.